Male-on-Male Intimate Partner Violence and Sexual Risk Behaviors Among Money Boys and Other Men Who Have Sex With Men in Shanghai, China - Dunkle, Kristin L. (Sex Transm Dis, 2013)
BACKGROUND: Intimate partner violence (IPV) is known to increase HIV risk among heterosexual women, but less is known about IPV and HIV among men who have sex with men (MSM), with almost no data from non-Western countries. This study examined the prevalence of IPV and links between IPV and HIV risks among MSM in Shanghai, China. METHODS: A cross-sectional sample of 404 money boys (male sex workers) and other MSM were recruited via respondent-driven sampling. RESULTS: Overall, 51% of the sample reported emotional, physical, or sexual abuse from a male sexual partner. Money boys reported more overall abuse than did other MSM, and more were likely than other MSM to report experiencing multiple types of abuse. MSM who reported violence or abuse from male partners reported more overall sexual risk behavior, and specifically, more unprotected sex and more sex linked to alcohol and other substance use. The association between experience of abuse from male partners and increased HIV risk did not differ between money boys and other Chinese MSM. CONCLUSIONS: We conclude that violence and abuse from male partners are highly prevalent among Chinese MSM, and that experience of violence from male sexual partners is linked to increased HIV risk. HIV prevention targeting Chinese MSM must address the increased risk associated with experience of male-on-male IPV. Future research should explore links between HIV risk and MSM’s perpetration of violence against male partners, as well as exploring the role of violence in the male-female relationships of men who have sex with and men and women.